Sinergi Tokoh Masyarakat Dan Pendidikan Dalam Pembentukan Akhlak Islami - Asman, Yunita; Rasyidin; Abdi, Dira; Mawaadah; Amira, Nurul (Yayasan Cendekia Gagayunan Indonesia, 2024)
Islamic moral education is a crucial aspect in shaping a society's character to be ethical and civilized. In Empai Tanong Village, Montasik District, Aceh Besar, the synergy between community leaders and formal educational institutions has proven to be effective in the formation of Islamic ethics. This study aims to explore the role of collaboration between formal and informal education, carried out by community leaders, in reinforcing Islamic moral values in the local community. The research uses a qualitative approach, with in-depth interviews with community leaders, educators, and local residents. The findings indicate that formal education and the teachings from community leaders complement each other, with religious education in schools providing the theory and concepts of Islamic ethics, while community leaders instill these values through example and religious activities. The family and social environment also play an important role in supporting the formation of Islamic ethics, although challenges from social media and external cultural influences remain obstacles. This study emphasizes the importance of synergy between educational institutions, community leaders, and families in creating a community with Islamic ethics in Empai Tanong Village.